Luxembourg : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that with a strong policy framework, Luxembourg has weathered the crisis well and the economy is rebounding. The fiscal position remains sound, and the large financial sector has been resilient. After a shallow recession in 2012, growth reached 2.1 percent in 2013. The improving economic and financial environment in Europe drove the recovery in services exports. The outlook is for growth to firm up but without returning to its pre-crisis trend. Output is forecast to grow broadly in line with potential (2 to 2 1\2 percent) during 2014-2019.